2018
DOI: 10.1016/j.jamda.2017.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Controlled Study Comparing a DPP4 Inhibitor (Linagliptin) and Basal Insulin (Glargine) in Patients With Type 2 Diabetes in Long-term Care and Skilled Nursing Facilities: Linagliptin-LTC Trial

Abstract: Treatment with linagliptin resulted in noninferior glycemic control and in significantly lower risk of hypoglycemia compared to insulin glargine in long-term care and skilled nursing facility residents with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 39 publications
(56 reference statements)
1
35
0
1
Order By: Relevance
“…Linagliptin has previously shown glucose-lowering efficacy and safety in multiple clinical trials. 9,29,36 From a pharmacological perspective, linagliptin is the only DPP-4 inhibitor excreted primarily via the bile, rather than the kidney, with kidney excretion accounting for only 5% of the dose. Therefore, no dose adjustment is required in patients with reduced kidney function, even at severe stages.…”
Section: Overall Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Linagliptin has previously shown glucose-lowering efficacy and safety in multiple clinical trials. 9,29,36 From a pharmacological perspective, linagliptin is the only DPP-4 inhibitor excreted primarily via the bile, rather than the kidney, with kidney excretion accounting for only 5% of the dose. Therefore, no dose adjustment is required in patients with reduced kidney function, even at severe stages.…”
Section: Overall Safetymentioning
confidence: 99%
“…Notable deleterious effects caused by hypoglycaemia are cardiac arrhythmias, and altered mental status and cognition, which can, in turn, lead to falls and fractures . Furthermore, hospitalization as a result of hypoglycaemia in older people is associated with a substantial increase in morbidity and mortality . Consequently, guidelines for older adults emphasize minimizing the risk of hypoglycaemia …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linagliptin, an orally active small‐molecule inhibitor of DPP‐4, licensed in the USA in 2011, has been shown to improve glycaemic control in adults with T2D . It is not necessary to modify the dose of linagliptin based on renal function; therefore, it is an ideal agent for use in the setting of hospitals and long‐term care facilities . We hypothesized that use of linagliptin, with correction doses of rapid‐acting supplemental insulin, would result in non‐inferior glycaemic control as compared with a basal‐bolus insulin regimen in non‐cardiac surgical patients with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the present study showed DPP‐4i was used in 67.6% of residents among those using any antidiabetic medicines in Japanese nursing homes, whereas its use is rare in other countries . A recent randomized controlled study showed that treatment with linagliptin, a DPP‐4i, resulted in a significantly lower risk of hypoglycemia and non‐inferior glycemic control compared with insulin glargine in nursing facilities in the USA …”
Section: Discussionmentioning
confidence: 67%